2013
DOI: 10.2754/avb201382040369
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of ESR, FSHß, RBP4, PRL, OPN genes and their influence on morphometric traits of gilt reproductive tract before sexual maturity

Abstract: The aim of the study was to examine the effect of gene polymorphism on the development of the reproductive system in 100 Polish Large White and 100 Polish Landrace gilts. Gilts were slaughtered when they reached 100 kg, and their uterus weight and length, as well as the ovary weight and volume were evaluated. Differences between gilts of both breeds were observed in some traits of the reproductive system, such as the uterine weight without the broad ligament (P ≤ 0.05) and the uterine capacity (P ≤ 0.01). Poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Similar allelic frequencies have been reported for Large White and Landrace × Large White populations [ 1 , 7 , 12 14 ] and in Black Slavonian sows [ 15 ]. Higher allelic values for A allele have been previously reported in Duroc [ 16 ] and in Polish Landrace [ 17 ] sows populations, while lower values have been reported by Kapelański et al [ 18 ] in Polish Landrace and in Police Large White populations. The analyzed population was found to deviate from the Hardy-Weinberg equilibrium due to the higher value of heterozygous genotype, as also reported by Omelka et al [ 19 ].…”
Section: Discussionmentioning
confidence: 80%
“…Similar allelic frequencies have been reported for Large White and Landrace × Large White populations [ 1 , 7 , 12 14 ] and in Black Slavonian sows [ 15 ]. Higher allelic values for A allele have been previously reported in Duroc [ 16 ] and in Polish Landrace [ 17 ] sows populations, while lower values have been reported by Kapelański et al [ 18 ] in Polish Landrace and in Police Large White populations. The analyzed population was found to deviate from the Hardy-Weinberg equilibrium due to the higher value of heterozygous genotype, as also reported by Omelka et al [ 19 ].…”
Section: Discussionmentioning
confidence: 80%
“…The association between Estrogen Receptor (ESR), Follicle Stimulating Hormone Beta (FSHB) and Prolactin Receptor (PRLR) polymorphisms and reproductive traits in gilts and sows was reported in previous studies (Rothschild et al 1996;van Rens et al 2002;Korwin-Kossakowska et al 2003;Kapelański et al 2013;Hunyadi-Bagi et al 2016;Vega et al 2018;Melnikova et al 2019). For ESR, the presence Effect of ESR, FSHB and PRLR Genes on Sperm Traits of Landrace and Yorkshire Boars in the Tropical Environmental... of allele B was significantly associated with an increased litter size (Rothschild et al 1996;Short et al 1997;Melnikova et al 2019).…”
Section: Introductionmentioning
confidence: 82%
“…Similarly, Korwin-Kossakowska et al (2003) reported allele A frequencies of more than 0.90 in a synthetic pig line, which was selected for reproductive traits. In contrast, studies of Kapelański et al (2013) and Polasik et al (2016) showed that BB genotype in Landrace gilts was predominant. In the last two study, the frequency of BB was more than 0.82.…”
Section: Genotype Frequenciesmentioning
confidence: 88%
“…The SINE polymorphisms at intron 6 of the porcine OPN gene were found to be associated with litter size as well as body weight at birth and weaning traits Niu et al, 2008;Zhang et al, 2010). These SINE polymorphisms were found to be associated with the uterine weight in Polish Landrace pigs (Kapelanski et al, 2013). Moreover, two synonymous SNP (c.559A>C and c.574C>G) of the porcine OPN gene were associated with their expres- sion levels in uterine tissues (Korwin-Kossakowska et al, 2013).…”
Section: Discussionmentioning
confidence: 99%